Analisis Minat Belajar Siswa Terhadap Pembelajaran PJOK Materi Futsal pada SMP Negeri 2 Pattallassang Kabupaten Gowa - Hasanuddin, Muh. Reyhan Fias; Istiqamah, Nur; R, Andi Fathir Perawira.; Sophia; Budianto; Sir, Irvan; Arfanda, Poppy Elisano (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the level of interest in learning PJOK (Physical Education) for futsal among students in Year 8 at SMP Negeri 2 Pattallassang, Gowa Regency. The study used a quantitative descriptive approach with a survey method. The sample size was 28 students, selected using random sampling. The instrument used was a questionnaire on learning motivation, which was designed based on the indicators of attention, interest, enjoyment, and involvement of students, with measurement using a Likert scale. Data collection was carried out by distributing the questionnaire to the respondents, and then analysed using descriptive statistics in the form of percentages with the help of SPSS version 29.0 and Microsoft Excel 2023. The results of the study showed that student interest was in the 'very low' category at 10%, 'low' at 17%, 'moderate' at 32%, 'good' at 39%, and 'very good' at 0%. Despite the presence of students with low learning motivation, the average score of 94.86 indicates that, in general, students' learning motivation for the futsal PJOK subject is in the good category. This finding implies that PE teachers need to maintain and improve their varied and engaging teaching strategies to ensure that students' learning motivation is more evenly distributed and improves, particularly among those who are still in the lower category.